How quickly do physicians adopt new drugs? The case of second-generation antipsychotics - Huskamp, Haiden (2013)
OBJECTIVE: To examine physician adoption of second-generation antipsychotic medications and identify physician-level factors associated with early adoption. METHODS: Using IMS Health Xponent™ data, which captures over 70% of all prescriptions filled in the U.S., and AMA Masterfile data on prescriber characteristics for each of 9 second-generation antipsychotics introduced from 1996–2008 for 30,369 physicians who prescribed antipsychotics, we estimate drug-specific Cox proportional hazards models of time to adoption and conduct descriptive analysis of the total number of agents prescribed. RESULTS: On average, physicians waited two or more years before prescribing new second-generation antipsychotics, but there was substantial heterogeneity across products in time to adoption. General practitioners were much slower to adopt second-generation antipsychotics than psychiatrists (hazard ratios (HRs) ranged from 0.10–0.35); solo practitioners were slower to adopt most products than group practitioners (HRs ranged from 0.77–0.89). Physicians in the highest quartile of antipsychotic prescribing volume adopted second-generation antipsychotics much faster than physicians in the lowest quartile (HRs ranged from 0.15–0.39). Psychiatrists tended to prescribe a broader set of antipsychotics (median of 6) than other specialties (median of 2 for general practitioners and neurologists and 1 for pediatricians). CONCLUSIONS: Policymakers are searching for ways to control rapid health spending growth, which is driven primarily by use of new technologies such as second-generation antipsychotics. Understanding the factors that influence physician adoption of new medications will be crucial in the implementation of efforts aimed at maximizing value of care received by individuals with mental disorders as well as efforts to improve medication safety.